2016
DOI: 10.1093/carcin/bgw091
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of ST6Gal I enhances colorectal cancer metastasis by down-regulating KAI1 via exosome-mediated exportation and thereby rescues integrin signaling

Abstract: Aberrant sialylation has long been correlated with human cancer. Increased ST6 Gal I (β-galactoside α 2, 6 sialyltransferase) and consequently higher levels of cell-surface α 2, 6 sialylation has been associated with human colorectal cancer (CRC) metastasis. We have extensive circumstantial data that sialylation is connected to cancer metastasis, but we do not understand in detail how sialylation can switch on/off multiple steps in cancer metastasis. To investigate the molecular mechanism underlying the ST6Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The effect of specific N-glycosylation events varies, with some promoting tumor progression, while others limit progression/metastases. Elevated expression of ST6GAL1 has previously been observed in multiple types of adenocarcinomas and linked to both worsened and improved outcomes (57,58). These contradictory observations may relate to differences in cancer mucin expression and/or effect on PI3K/Akt-related proliferation pathways (59,60).…”
Section: Discussionmentioning
confidence: 97%
“…The effect of specific N-glycosylation events varies, with some promoting tumor progression, while others limit progression/metastases. Elevated expression of ST6GAL1 has previously been observed in multiple types of adenocarcinomas and linked to both worsened and improved outcomes (57,58). These contradictory observations may relate to differences in cancer mucin expression and/or effect on PI3K/Akt-related proliferation pathways (59,60).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have indicated a correlation between ST6Gal-I activity and cancer metastasis, while in others such correlation has not been found [46]. There are also other studies, showing that ST6Gal-I overexpression changes cellular phenotype or behavior, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Sialylation regulates numerous cellular processes, including cell–cell communication, immune surveillance, defense against pathogens and cancer progression and metastasis [46,53]. In cancers, especially α-2,6-sialylation is increased and correlates with increased cell proliferation, migration, invasion and metastasis, while inhibiting apoptosis [[47], [48], [49], [50]].…”
Section: Discussionmentioning
confidence: 99%
“…They export the protein via EVs, as indicated by EVs that are more enriched in PABP1 as compared to EVs from normal AZ-521 cells. Colorectal cancer cells were also found to export, KAI1 (CD82), a suppressor of tumor metastasis, via EVs as a cell-autonomous mechanism to enhance metastasis [7174]. However, further exploration of this mechanism is necessary to develop therapeutics that can inhibit EV-mediated secretion of tumor suppressors.…”
Section: Role Of Ev Cargo In Metastatic Processesmentioning
confidence: 99%